Heavy metal pollution in Guangdong Province, China, and the strategies to manage the situation - Wang, Yutao; Björn, Lars Olof (Frontiers in Environmental Science, 2014)
Guangdong Province in China runs a risk of gradually increasing pollution of its agricultural land and, as a consequence, toxic agricultural products. We concentrate here on the situation for cadmium, copper and lead. For these metals we describe the toxicology, the current pollution and its sources, and what can be done to improve the situation by cleaning the soil from pollutants, choice of crops which allocate a minimum of the metals to edible parts, and switching to non-food crops when other measures do not guarantee food safety.